Evaluation and Mitigation of Android Application in PT. Aku Pintar Indonesia - Lutvianto Pebri Handoko; Mokh. Suef (Institut Teknologi Sepuluh Nopember, 2019)
Aku Pintar Indonesia enterprise is one of the educational start-up industries currently developing an Android-based system. System errors could appear in various both the features and administrative processes. The system repair priority could be given to the easiest system error first without taking into account the risk that would arise. The company needed to change its risk management by providing the priority of system repair and considering the effects and frequency of the occurrences. This research aims to help Aku Pintar Indonesia enterprise in choosing the priority of system error repair in order to improve their services to their users. This research used FMEA which allows the risk level of each error modes being assessed. System errors and its frequency were identified by web-based Google Play Console. The disadvantage level appeared from each errors determined by utilizing expert judgment in a Focus Group Discussion (FGD). The risk level of each system errors determined by the frequency of each and the level of the disadvantages, then measure the value of the Risk Priority Number by multiplying the results of severity and occurrence so that the risk value is obtained. The next process of risk mapping based on the risk level uses a modification of the risk mapping table to obtain the error rate for making priority improvements. This research produced a complete document that contains the information needed to plan and prevent repetitive errors, and can reduce the initial system error rate by 4% to 2.4% according to reports from the Google Play Console system